Experimental testing of fracture fixation plates: A review. (September 2022) - Zhang, Shiling; Patel, Dharmesh; Brady, Mark; Gambill, Sherri; Theivendran, Kanthan; Deshmukh, Subodh; Swadener, John; Junaid, Sarah; Leslie, Laura Jane
Metal and its alloys have been predominantly used in fracture fixation for centuries, but new materials such as composites and polymers have begun to see clinical use for fracture fixation during the past couple of decades. Along with the emerging of new materials, tribological issues, especially debris, have become a growing concern for fracture fixation plates. This article for the first time systematically reviews the most recent biomechanical research, with a focus on experimental testing, of those plates within ScienceDirect and PubMed databases. Based on the search criteria, a total of 5449 papers were retrieved, which were then further filtered to exclude nonrelevant, duplicate or non-accessible full article papers. In the end, a total of 83 papers were reviewed. In experimental testing plates, screws and simulated bones or cadaver bones are employed to build a fixation construct in order to test the strength and stability of different plate and screw configurations. The test set-up conditions and conclusions are well documented and summarised here, including fracture gap size, types of bones deployed, as well as the applied load, test speed and test ending criteria. However, research on long term plate usage was very limited. It is also discovered that there is very limited experimental research around the tribological behaviour particularly on the debris' generation, collection and characterisation. In addition, there is no identified standard studying debris of fracture fixation plate. Therefore, the authors suggested the generation of a suite of tribological testing standards on fracture fixation plate and screws in the aim to answer key questions around the debris from fracture fixation plate of new materials or new design and ultimately to provide an insight on how to reduce the risks of debris-related osteolysis, inflammation and aseptic loosening.